1992
DOI: 10.2165/00002018-199207030-00003
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of Local Anaesthetics

Abstract: Local anaesthetics are responsible for 5 to 10% of all reported adverse reactions to anaesthetic drugs. Adverse effects may be classified as: (a) those associated directly with blocking ion channels in cell membranes, such as cardiovascular and CNS toxicity; (b) those due to other effects of drug or vehicle (mainly peripheral nerve complications); (c) allergic reactions (often a mistaken diagnosis); and (d) mechanical or other effects of technique, such as needle trauma or introduction of infection. Signs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0
3

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(49 citation statements)
references
References 71 publications
1
45
0
3
Order By: Relevance
“…Transient loss of vision with an afferent pupillary defect has also been associated with intracameral lidocaine (9). Lidocaine is potentially toxic both systemically and to the optic nerve (10,11). There are no reports to date describing retinal pathology associated with intracameral lidocaine.…”
Section: Introductionmentioning
confidence: 99%
“…Transient loss of vision with an afferent pupillary defect has also been associated with intracameral lidocaine (9). Lidocaine is potentially toxic both systemically and to the optic nerve (10,11). There are no reports to date describing retinal pathology associated with intracameral lidocaine.…”
Section: Introductionmentioning
confidence: 99%
“…Bupivacaine was administered epidurally in conjunction with induced labor to simulate obstetric use. Brain and heart were selected for analysis because they are potential sites for bupivacaine effects on ion channels and conduction [20,21]. Liver was also analyzed because it is the major site of bupivacaine metabolism in humans.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, bupivacaine only displays a weak and no significant activity on TNBS-induced colitis at 10mg/kg/d, and toxicity at higher dose. Cardiotoxicity of bupivacaine when overdosed is well documented (McCaughey, 1992) and association with ketamine had been described to lead to a possible inhibition of the metabolism of bupivacaine (Gantenbein et al, 1997) which could explain the observed toxicity under our experimental conditions.…”
Section: Discussionmentioning
confidence: 71%